Ranking of performance indicators in an Internet of Things (IoT)-based traceability system for the agriculture supply chain (ASC). Issue 3 (6th October 2021) - Yadav, Sanjeev; Garg, Dixit; Luthra, Sunil
Abstract : Purpose: The prime aim of this paper is the identification and prioritization of performance indicators, which motivate the development of an Internet of Things (IoT)-based traceability system for the agriculture supply chain (ASC). Also, this research aims for checking the robustness of obtained results. Design/methodology/approach: Ten performance indicators have been identified based on the five "criteria in the IoT-based traceable system". Further, based on five criteria, performance indicators were ranked by using grey-based "Additive Ratio Assessment". Findings: Sustainable practices obtained first rank, and certification of agri-products obtained worst ranking. Further, based on sensitivity analysis, tracking of agri-products and stakeholders' behavior have found high sensitivity. Also, information sharing and global distribution networks have found the least sensitive performance indicators. Research limitations/implications: This research has some limitations of taking only a few criteria and alternatives. This study may also contribute as a practical insight to the practitioners and managers in decision-making in the adoption of an IoT-based traceable system within the ASC. Originality/value: This research may motivate the implementation of an IoT-based efficient traceability mechanism that improved the sustainability and consumer's trust in the ASC during different types of hazardous activities and other outbreaks (COVID-19). Also, this research has provided a theoretical insight based on the dynamic capability theory (DCT).